INTERPRETASI ETIKA PROFESI DALAM UPAYA PENINGKATAN KEPERCAYAAN PUBLIK TERHADAP PROFESI HUKUM - Wardani, Ach. Khiarul Waro (Universitas Muara Bungo, 2025)
The interpretation of professional ethics in this study discusses how law enforcers make efforts to restore public trust in the law and the legal profession. The background of this study is social issues about law enforcers, the role of law enforcers is considered not to side with the truth but with profit, so that some people consider the legal profession not to be law enforcers but rather a legal business. The behavior of violating legal ethics makes the legal principles of certainty, justice and legal benefits cannot be felt by some legal subjects (society). The purpose of this study is to demand that legal professions better understand and dare to practice ethics and professional codes of ethics in everyday life and be able to restore public trust in the legal profession. This study uses normative juridical legal methods through library data, regulations related to issues and problems that occur in the field. The results of this study are 1). With the interpretation of professional ethics, legal professions can implement legal services in accordance with the code of ethics and principles of law enforcers to create certainty, justice and benefits for the community, 2). Public trust will increase in the legal profession as law enforcers who can protect the community. The negative impact of the legal profession's inability to implement ethics and codes of ethics for the legal profession will result in a loss of public trust in law enforcement itself.